2011
DOI: 10.1073/pnas.1014448108
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric signal transmission in the nucleotide-binding domain of 70-kDa heat shock protein (Hsp70) molecular chaperones

Abstract: The 70-kDa heat shock protein (Hsp70) chaperones perform a wide array of cellular functions that all derive from the ability of their N-terminal nucleotide-binding domains (NBDs) to allosterically regulate the substrate affinity of their C-terminal substrate-binding domains in a nucleotide-dependent mechanism. To explore the structural origins of Hsp70 allostery, we performed NMR analysis on the NBD of DnaK, the Escherichia coli Hsp70, in six different states (ligand-bound or apo) and in two constructs, one th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
198
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(228 citation statements)
references
References 41 publications
29
198
0
Order By: Relevance
“…Our dose responses further showed that, as suggested from the crystal structure of yeast Hsp110 with bovine Hcp70 NBD, equimolar Hsp70 and Hsp110 can optimally refold stable aggregated luciferase, likely by binding to orthologous topological sites in their respective NBDs and by effective reciprocal allosteric signals of similar quality and intensities between the two orthologous SBDs (42). The presence of such symmetrical allosteric signals was confirmed by the reciprocal release of the unfolded luciferase that we observed in the presence of apyrase, upon addition of Hsp110 to stable preformed ADP-Hsp70-Luc complexes or symmetrically of Hsp70 to stable preformed ADP-Hsp110-Luc complexes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our dose responses further showed that, as suggested from the crystal structure of yeast Hsp110 with bovine Hcp70 NBD, equimolar Hsp70 and Hsp110 can optimally refold stable aggregated luciferase, likely by binding to orthologous topological sites in their respective NBDs and by effective reciprocal allosteric signals of similar quality and intensities between the two orthologous SBDs (42). The presence of such symmetrical allosteric signals was confirmed by the reciprocal release of the unfolded luciferase that we observed in the presence of apyrase, upon addition of Hsp110 to stable preformed ADP-Hsp70-Luc complexes or symmetrically of Hsp70 to stable preformed ADP-Hsp110-Luc complexes.…”
Section: Discussionmentioning
confidence: 94%
“…The chaperone mechanism of Hsp70 has been extensively studied (42). Bacterial DnaK was shown to use ATP to apply an unfolding force on stable misfolded polypeptides and small aggregates by two complementary mechanisms likely involving both direct "clamping" by individual DnaK molecules that may unfold non-native ␤-structures in stable misfolded polypeptides (12,43) and indirect "entropic pulling" by several concomitantly clamped DnaK molecules on the same misfolded polypeptide, cooperating to unfold by thermal movements local misfolded regions in between chaperone-bound segments (44).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two independent reports have showed that the binding of Hsp70s to BMP and SGC Mamelak and Lingwood 2001) is mediated by amino acids different than the ones known to bind to ATP or ADP. These two arguments favor the second explanation suggesting that changes of the conformation and oligomerization protein states caused by nucleotide-binding (Young 2010;Zhuravleva and Gierasch 2011) are responsible for the observed reduction in lipid binding. The second explanation is also favored by the fact that HspA1A embeds in PS liposomes via its SBD region (Armijo et al 2014), and the finding that ATP and ADP strongly inhibit sulfatide-induced formation of the HspA1A oligomers only in the presence of KCl (Harada et al 2015).…”
Section: Discussionmentioning
confidence: 94%
“…However, the current understanding of the allosteric role of partially unstructured linkers is at best scant. Although the role of covalent linkage in colocalization of protein domains is well known, it has recently been hypothesized that linkers, although generally quite flexible, have evolved to serve not simply as passive covalent threads connecting one domain to the next (i.e., "beadson-a-string" model), but also as active components of functionally relevant allosteric networks (22)(23)(24)(25). To test this hypothesis, here we have investigated the allosteric role of a critical linker in the regulatory subunit (R) of protein kinase A (PKA).…”
mentioning
confidence: 99%